First-principles calculations and Raman scattering evidence for local symmetry lowering in rhombohedral ilmenite: Temperature- and pressure-dependent studies - Rodrigues, J. E.; Ferrer, M. M. [UNESP]; Cunha, T. R.; Costa, R. C.; Sambrano, J. R. [UNESP]; Rodrigues, A. D.; Pizani, P. S. (IOP Publishing, 2018)
ATiO3-type materials may exist in two different crystalline forms: the perovskite and ilmenite. While many papers have devoted their attention to evaluating the structural properties of the perovskite phase, the structural stability of the ilmenite one still remains unsolved. Here, we present our results based on the lattice dynamics and first-principles calculations (density functional theory) of the CdTiO3 ilmenite phase, which are confronted with experimental data obtained through micro Raman spectroscopy that is a very good tool to probe the local crystal structure. Additional Raman bands, which are not foreseen from group-theory for the ilmenite rhombohedral structure, appeared in both low temperature (under vacuum condition) and high-pressure (at room temperature) spectra. The behavior can be explained by considering the local loss of inversion symmetry operation which reduces the overall space group from R3 (C23i) to (C4 3). Our results can also be extended to other ilmenite-type compositions.
Keywords: CdTiO3; density functional theory; factor group analysis; ilmenite; inversion operation; Raman spectroscopy